Strategi Pembelajaran dengan Memadukan Teknologi dan Media - Agung Wahyudi; Linda Linda; Ali Akbar Jono (GHAITSA : Islamic Education Journal, 2023)
Learning strategy is planning about a series of activities designed in an effort to achieve certain educational goals. In this case, learning strategies become activities that must be carried out by teachers and students. The reason is, the learning strategy is also interpreted as a set of learning materials and procedures to generate learning outcomes in students. In its implementation, learning strategies consist of various kinds of learning techniques and methods, for example reading, remembering, repeating, and applying information. According to the 1970 Commission Instruction Technology (CIT) definition, learning technology is defined as a medium that was born as a result of the communication revolution that can be used for learning purposes in addition to teachers, textbooks, and blackboards….the parts that make up learning technology are television, film, OHP , computers and other hardware and software parts. Schramm (1977) suggests that learning media is a message carrier technology that can be utilized for learning purposes. Meanwhile, Briggs (1977) argues that learning media are physical means for conveying learning content/material such as: books, films, videos and so on. Meanwhile, the National Education Association (1969) revealed that learning media is a means of communication in print and audio-visual form, including hardware technology. From the three opinions above, it can be concluded that learning media is anything that can convey messages, can stimulate the thoughts, feelings, and willingness of students so that they can encourage the creation of learning processes in students.